(untitled) (Window of Public Health Journal, 2026)
New students are in a transition phase from adolescence to early adulthood, marked by changes in the learning environment, social roles, and demands for independence. The change in status to new students often triggers stress due to academic and psychological adjustments. This is a concern for students in the D4 Health Promotion Study Program. Mental health is a fundamental component in developing prospective health promotion workers, as this profession requires the ability to manage stress, maintain psychological well-being, and serve as a role model for healthy living behaviors. This study aims to describe the stress levels of new students in the D4 Health Promotion Study Program. This study was conducted at the Faculty of Sport and Health Sciences, Makassar State University, D4 Health Promotion Study Program. This study used a quantitative descriptive design with a cross-sectional approach. Respondents in this study were first-semester students in the 2025/2026 academic year in the D4 Health Promotion Study Program. Stress levels were measured using the Perceived Stress Scale (PSS) questionnaire. The results showed that the majority of respondents were in the moderate stress category (81.7%), while a small portion were in the mild stress category (11.7%) and severe stress (6.7%). These findings underscore the importance of early mental health support and encourage collaboration among educators and health professionals to enhance student well-being and professional growth.